Aquisição fonológica de fricativas por crianças com transtorno fonológico: uma investigação acústica - Corrêa, Alessandra Pagliuso dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The present study focuses on the presence of covert contrasts in the speech of children with phonological disorder. The covert contrasts are described in the literature as productions that, despite showing auditory perception results identical/similar reveal, from the acoustic analysis, subtle differences. More specifically, this study to observe whether there is a preference, on the part of children with phonological disorders, on the manipulation of acoustic cues that are not robust to Brazilian Portuguese in an attempt to distinguish the fricative phones. Five audio recordings of the speech of five children with speech disorder between 4 and 5 years old who presented the so-called phonic substitution involving the sound class of the fricatives were used. These data were collected using the Speech Assessment Instrument for Acoustic Analysis – SAIAA (IAFAC), recorded in a soundproof booth, requesting each child five repetitions out of the 96 words that make up the instrument. The data were edited and analyzed using the software PRAAT. A phonetic transcription of the first repetition (R1) of each child were performed by three judges and considered the agreement of 66%. From this transcription the degree of severity of phonological disorder was calculated through the PCC-R. Posteriorly, contrastive phonological analysis of the production of the five children was carried out and, finally, acoustic analysis of all the substitutions was performed involving the sound class of the fricatives. For the acoustic analysis the following parameters were used: the lower limit of the spectral peak, centre of gravity, variance, skewness, kurtosis and duration. After acoustic analysis, we could verify the existence of covert contrast in the productions as homophones aurally taken by the judges, representing a total of 54% of total substitutions identified through impressionistic approach by the judges ...

O presente trabalho versa sobre a presença de contrastes encobertos na fala de crianças com transtorno fonológico. Na literatura, os contrastes encobertos são descritos como produções que, apesar de apresentarem resultados perceptivo-auditivos idênticos/semelhantes, revelam, a partir da análise acústica, diferenças sutis. De maneira mais específica, este estudo busca observar se há preferência, por parte das crianças com transtorno fonológico, pela manipulação de pistas acústicas que não são robustas para o Português Brasileiro, na tentativa de distinguir os fones fricativos. Para tanto, foram utilizadas cinco gravações em áudio, da fala de cinco crianças entre 4 e 5 anos com transtorno fonológico, que apresentavam as chamadas “substituições fônicas” envolvendo a classe de sons das fricativas. Os dados foram coletados utilizando-se o Instrumento para Avaliação de Fala para Análise Acústica – IAFAC, gravados em cabine acústica, socilitando a cada criança cinco repetições das 96 palavras que compõem o instrumento. Os dados foram editados e analisados com o uso do software PRAAT. Foi realizada uma transcrição fonética da primeira repetição (R1) de cada criança, por três juízes, e considerada a concordância de 66%. A partir desta transcrição, foi realizado o cálculo do grau de severidade do transtorno fonológico por meio do PCC-R. Em seguida, realizaram-se a análise fonológica contrastiva da produção das cinco crianças e a análise acústica de todas as “substituições” envolvendo a classe de sons das fricativas. Para a análise acústica, os seguintes parâmetros foram adotados: limite inferior do pico espectral, centróide, variância, assimetria, curtose e duração. Após a análise acústica, verificou-se a existência de contrastes encobertos nas produções tidas como homófonas auditivamente, representando um total de 54% do total das ...
Keywords: Linguística; Fonética acústica; Distúrbios da articulação em crianças; Aquisição da linguagem; Disturbios da fala; Língua portuguesa - Português falado - Brasil; Phonetics, Acoustic